Elevated serum CD40 as a potential biomarker for the differential diagnosis of acute thyrotoxic myopathy - Chunjiao Wu; Yun Zhang; Tingliang Wang; Meiyu Gan; Jingyi Qin; Zuojie Luo (Scientific Reports)
Abstract Acute thyrotoxic myopathy (ATM) is a rare yet severe complication of thyrotoxicosis that affects the central nervous system and is associated with a high mortality rate if not diagnosed and treated promptly. Currently, the diagnosis of ATM primarily relies on clinical manifestations, and there is a lack of specific serological markers to support the diagnostic process. This study aimed to investigate the differences in serum CD40 levels between patients with acute thyrotoxic myopathy (ATM), those with Graves’ disease, and healthy controls, and to evaluate its potential as a diagnostic biomarker for differentiating ATM. Additionally, the study examined the correlation between serum CD40 levels and various parameters, including the ATM symptom score (ATMSS), FT3, FT4, TSH, TGAb, TRAb, and TPOAb. This retrospective cross-sectional study included 17 patients with ATM, 17 patients with Graves’ disease, and 17 healthy controls, all recruited from the First Affiliated Hospital of Guangxi Medical University between January 2022 and August 2024. Clinical evaluations, serum thyroid hormone and related antibody testing, and CD40 level measurements were conducted. The predictive value of CD40, FT3, FT4, TSH, TGAb, TRAb, and ATMSS for ATM was assessed using receiver operating characteristic (ROC) curve analysis. Spearman correlation analysis was performed to explore the relationship between CD40 levels and ATMSS, FT3, FT4, TSH, TGAb, TRAb, and TPOAb. Serum levels of CD40[259.17(227.50,378.03)vs.190.71(174.08,198.96)vs. 166.98(142.94,175.90)], FT3[28.34(17.13,37.65) vs. 8.82(6.36,21.00) vs. 5.02(3.93,5.45)], and FT4 [67.58(37.53,77.23)vs.27.03(15.96,47.05)vs.16.82(13.59,17.90)]in ATM patients were significantly higher than those in Graves’ disease patients and the control group, with statistically significant differences (P < 0.01). ROC analysis demonstrated that CD40 has high predictive value for distinguishing between GD and ATM, with an area under the curve (AUC) of 0.99, and both sensitivity and specificity of 94.1%. Correlation analysis revealed a positive correlation between CD40 and the ATM symptom score (ATMSS) (r = 0.72, P < 0.01). Positive correlations were also observed between CD40 and FT3 (r = 0.53, P < 0.01) and FT4 (r = 0.56, P < 0.01). TSH showed a negative correlation trend with CD40 (r = -0.21, P = 0.23), but this difference was not statistically significant. No significant correlations were found between CD40 and TGAb (r = 0.10, P = 0.59), TRAb (r = 0.26, P = 0.13), or TPOAb (r = 0.06, P = 0.72). Elevated serum CD40 levels are associated with the severity of ATM symptoms and may serve as a potential biomarker for ATM. The role of CD40 as an adjunct in the early diagnosis of ATM holds clinical significance, offering new insights into the differential diagnosis and treatment of ATM.